Design and Build of a Blynk-Based Automatic Cat Food and Drinking Water Dispenser - Gus Erniati Ani; Firdaus B; Yulindon (Politeknik Negeri Padang, 2024)
Abstract — There are many people who like to keep cats. When keeping cats, the things you need to pay attention to are eating and drinking so that the cat's health is maintained. As it should be, food and drinking water must be given according to the dosage. However, if the cat owner is outside the house, it will make it difficult for the owner to feed and drink it. Through this final project, cats can eat and drink at any time by implementing the Internet of Things called an automatic dispenser. Automatic food and drinking water dispenser uses NodeMCU8266, 2 servo motors, 2 ultrasonic sensors, HX711 load cell and Blynk software. The Blynk software functions to display the on/off switch, the distance the cat is approaching, the amount of food and drinking water available in the cat food and drinking water dispenser which is connected via nodeMCU8266 which can be accessed on the cat owner's smartphone. If the food and drinking water is less than capacity, a notification will immediately appear on the cat owner's smartphone and email.